Gastric polyps: a retrospective analysis of 26,000 digestive endoscopies Pólipos gástricos: análise retrospectiva de 26 000 endoscopias digestivas - Drausio Jefferson Morais; Ademar Yamanaka; José Murilo Robilotta Zeitune; Nelson Adami Andreollo (Arquivos de Gastroenterologia, 2007)
BACKGROUND: Gastric polyps are small gastric lesions, asymptomatic in most cases and are generally discovered inadvertently during upper digestive endoscopy. AIM: To retrospectively review the characteristics and frequency of gastric polyps, derived from the gastric mucosal epithelium in a large series of endoscopies. METHODS: One hundred and fifty three patients in a series of 26,000 consecutive upper digestive endoscopies done over a 5-year period, being that each patient had only one examination were analyzed and their histological and Yamada classification, as well as their location, size, histopathological findings and treatment studied. All patients had at least one gastric polyp, as confirmed by histological examination. RESULTS: The polyps were classified as hyperplastic, adenomatous and fundic gland polyps. The most of them measure less than 1 cm (hyperplastic polyps - 60,5%; adenomatous polyps - 73,6%; fundic gland polyps - 72%). Hyperplastic polyps were the most frequent and accounted for 71.3% of the cases, whereas fundic gland polyps accounted for 16.3% and adenomatous polyps for 12.4%. Hyperplastic and adenomatous polyps were primarily single, whereas fundic gland polyps tended to be multiple. A carcinoma was detected in one hyperplastic polyp (0.9%) and in two adenomatous polyps (10.5%). High grade dysplastic foci were found in four adenomatous polyps (21%). CONCLUSIONS: The digestive endoscopy is the safest and efficient method for the diagnosis of the gastric polyps, that in most of the patients does not show characteristic symptoms. The histopathological definition is not possible to the endoscopic glance being needed the pathologist's aid, once the conduct to be adopted will depend on the result of the biopsy. RACIONAL: Os pólipos gástricos são pequenas lesões gástricas, assintomáticos na maioria dos casos, e são diagnosticados por acaso durante a endoscopia digestiva alta. OBJETIVOS: Avaliar retrospectivamente as características e freqüência dos pólipos gástricos, oriundos da mucosa gástrica em uma casuística extensa de endoscopias digestivas. MÉTODOS: Cento e cinqüenta e três doentes em uma casuística de 26.000 endoscopias digestivas altas realizadas durante 5 anos, sendo que cada doente realizou apenas um exame, foram analisados quanto às características histopatológicas, classificação de Yamada, localização, tamanho e tratamento. Todos os casos tinham pelo menos um pólipo gástrico, confirmado pelo exame histopatológico de biopsia endoscópica. RESULTADOS: Os pólipos foram classificados como hiperplásicos, adenomatosos e de glândulas fúndicas. A maioria deles era menor que 1 cm (pólipos hiperplásicos - 60,5%; pólipos adenomatosos - 73,6%; pólipos de glândulas fúndicas - 72%). Os pólipos hiperplásicos foram os mais freqüentes e diagnosticados em 71,3% dos casos, enquanto os de glândulas fúndicas somaram 16,3% e os adenomatosos foram 12,4%. Os pólipos hiperplásicos e os adenomatosos, na maioria das vezes, foram únicos, enquanto os de glândulas fúndicas tenderam a ser múltiplos. Carcinoma foram detectados em um pólipo hiperplásico (0,9%) e em dois adenomatosos (10,5%). Focos de displasia de alto grau foram encontrados em quatro pólipos adenomatosos (21%). CONCLUSÕES: A endoscopia digestiva é o método mais seguro e eficiente para o diagnóstico dos pólipos gástricos, que na maioria dos doentes não apresenta sintomas característicos. A definição histopatológica não é possível ao olhar endoscópico, necessitando-se do auxílio do patologista, uma vez que do resultado da biopsia dependerá a conduta a ser adotada.